The Effect of Foaming Agent and Maltodextrin Concentrations on the Characteristics of Bidara Fruit Powder Drink, Strawberry and Butterfly Pea Flower - Nanda Mazidatu Zulfa; Ulya Sarofa (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This research aimed to determine the effect of the concentration of foaming agent and maltodextrin on the characteristics of bidara fruit powder drink, strawberry, and butterfly pea flower. The study used a completely randomized design (CRD) with two factors and three replications. Data analysis used ANOVA followed by Duncan multiple range test (DMRT) at 5% confidence level. The first factor was the concentration of the foaming agent (egg white) (5% (F1), 6% (F2), 7% (F3)). The second factor was the concentration of maltodextrin 7.5% (M1), 10% (M2) and 12.5% ​​(M3)). Parameters observed included moisture content, ash content, yield, pH value, antioxidant activity, vitamin C, solubility, color, and organoleptic analysis including taste, aroma and color. The results of the treatment of egg white and maltodextrin concentrations had a significant effect on water content, yield, pH, antioxidant activity, vitamin C, solubility, and color. The best treatment in this research was bidara fruit powder drink with a concentration of foaming agent (7%) and 12.5% ​​maltodextrin with 35% water content, 0.88% ash content, pH 5.95, 68.86% antioxidant activity, vitamin C 141 mg/100g, color L 3.15, a -0.20, b -2.55 and yield 25.33%, taste score 3.94 (like), aroma 1.19 (very dislike ), color 4.38 (like), and anthocyanin content 8.60 mg/L.